Integration of PBL-Based E-Modules in Physics Education: Improving Problem-Solving Skills on Static Fluid Concept - Yuliani, Hadma; Tiya Andani; Luvia Ranggi Nastiti (Universitas Muhammadiyah Makassar, 2025)
Developing students’ problem-solving skills is a central aim of modern science education, yet many learners continue to struggle when applying physics concepts to authentic situations. In Indonesia, this challenge remains urgent, as national and international assessments consistently highlight gaps in higher-order thinking and reasoning. Responding to this need, the present study sought to investigate the effectiveness of a problem-based learning (PBL)–based electronic module (e-module) designed around Polya’s four problem-solving stages in improving high school students’ abilities in the static fluid topic. Using a pre-experimental one-group pretest–posttest design, the study involved 28 students who completed validated pretest and posttest instruments aligned with Polya’s framework. Data were analyzed descriptively and inferentially through the Wilcoxon Signed-Rank Test, normalized gain (N-gain), and Cohen’s d effect size. The results showed a clear increase in mean scores from 47.91 on the pretest to 73.11 on the posttest, with all four indicators: understanding the problem, planning solutions, implementing strategies, and evaluating outcomes. The Wilcoxon test confirmed statistically significant improvements for all participants, with an effect size of 1.971 indicating a very large practical impact. These findings demonstrate that integrating PBL with structured digital scaffolding can meaningfully enhance students’ problem-solving skills. The novelty of this research lies in adapting Polya’s classic model into an interactive e-module format and embedding it within PBL to promote inquiry and reflection. Overall, the study contributes to physics education by providing evidence that digital PBL resources can narrow performance gaps and foster deeper, more equitable learning outcomes in line with 21st-century educational demands.